Soil hydromorphy and soil carbon: A global data analysis - Amendola, D. [UNESP]; Mutema, M.; Rosolen, V. [UNESP]; Chaplot, V. (Elsevier, 2018)
Wetland soils are an important component of the Global Carbon Cycle because they store about 20–25% of the terrestrial soil organic carbon (SOC). Wetlands occupy about 6% of the global land surface and any change in their use or management has potentially dramatic consequences on greenhouse gases emissions. However, the capacity of wetland soils to store carbon (C) differs from place to place due to reasons still not well understood. The objective of this review was to evaluate the global variations in wetlands SOC content (SOCC) and to relate it to key soil and environmental factors such as soil texture, intensity of soil hydromorphy, metallic element content and climate. A comprehensive data analysis was performed using 122 soil profiles from 29 studies performed under temperate, humid, sub-humid, tropical and sub-arctic conditions. The results point to average SOCC of 53.5 ± 15.8 g C kg−1 with a maximum of 540 g C kg−1. SOCC increased with increase in intensity of soil hydromorphy (r = −0.52), Al (r = 0.19) and Fe content (r = 0.21), and decreased with soil pH (r = −0.24). There was also a surprising tendency for intensity of soil hydromorphy, and thus SOCC, to decrease with increasing mean annual precipitation and soil clay content. These results contribute to a better understanding of the impact of soil hydromorphy in wetlands on organic C stabilization in the soils. However, further studies with additional information on soil bulk density to assess carbon C stocks, still need to be performed.
Keywords: Biogeochemical cycle; Climate change; Gleysols; Organic matter decomposition; Redoxymorphic features